Low value capacitance measurement system for the application of monitoring human body - Arshad, Atika; Tasnim, Rumana; Zahirul Alam, A. H. M.; Khan, Sheroz (Asian Research Publishing Network (ARPN), 2016)
The core focus of this work is to design and develop a reliable capacitance sensing system for measuring very small capacitive changes at low frequencies. The sensing system is applicable in monitoring and characterizing human body movement. The interface circuit measures very small capacitive variation. Some capacitive values have been fixed and the produced capacitive changes have been measured for validating the possibility to monitor and detect the presence of human bodies. A variation in capacitance causes a variation in the output voltage. Due to the variation of output voltages, the presence or absence of the human body can be detected. Primary simulation results show that the measurement of little capacitance variation using an interface circuit is precise and linear. With the presence of a human body in the area right above the sensor, a capacitance variation as well as output voltage can be observed.